Novel Semiquantitative Bone Marrow Oedema Score and Fracture Score for the Magnetic Resonance Imaging Assessment of the Active Charcot Foot in Diabetes. (5th November 2017) - Meacock, L.; Petrova, N. L.; Donaldson, Ana; Isaac, A.; Briody, A.; Ramnarine, R.; Edmonds, M. E.; Elias, D. A.
Abstract : There are no accepted methods to grade bone marrow oedema (BMO) and fracture on magnetic resonance imaging (MRI) scans in Charcot osteoarthropathy. The aim was to devise semiquantitative BMO and fracture scores on foot and ankle MRI scans in diabetic patients with active osteoarthropathy and to assess the agreement in using these scores. Three radiologists assessed 45 scans (Siemens Avanto 1.5T, dedicated foot and ankle coil) and scored independently twenty-two bones (proximal phalanges, medial and lateral sesamoids, metatarsals, tarsals, distal tibial plafond, and medial and lateral malleoli) for BMO (0—no oedema, 1—oedema < 50% of bone volume, and 2—oedema > 50% of bone volume) and fracture (0—no fracture, 1—fracture, and 2—collapse/fragmentation). Interobserver agreement and intraobserver agreement were measured using multilevel modelling and intraclass correlation (ICC). The interobserver agreement for the total BMO and fracture scores was very good (ICC = 0.83, 95% confidence intervals (CI) 0.76, 0.91) and good (ICC = 0.62; 95% CI 0.48, 0.76), respectively. The intraobserver agreement for the total BMO and fracture scores was good (ICC = 0.78, 95% CI 0.6, 0.95) and fair to moderate (ICC = 0.44; 95% CI 0.14, 0.74), respectively. The proposed BMO and fracture scores are reliable and can be used to grade the extent of bone damage in the active Charcot foot.